Breakout - Messner, Kate (Bloomsbury Children's Books, 2018)
"From multiple perspectives, tells of a time capsule project and the middle schoolers who contribute, including future journalist Nora Tucker and newcomer Elidee Jones, whose brother is in the local prison"--Provided by publisher.